Annual Plan Outlays 1975-76 Government of Punjab - Planning Commission (Planning Commission, 1975)
Agriculture, Minor Irrigation, Soil and Water Conservation, Animal Husbandry, Dairy Development, Fisheries, Forests, Community Development and Panchayats, Cooperation, Irrigation, Flood Control, Power, Standardisation, Village and Small Industries, Mining and Metallurgical Industries, Civil Aviation, Roads, Road Transport, Tourism.
Government of Punjab, Planning Department Punjab